A comparison of team-based learning and lecture-based learning on clinical reasoning and classroom engagement: a cluster randomized controlled trial - Ulfa, Yunefit; Igarashi, Yukari; Takahata, Kaori; Shishido, Eri; Horiuchi, Shigeko (BMC medical education, 2021)
Background The lecture-based learning (LBL) implemented in most Indonesian nursing/midwifery schools underlies the students’ lack of ability in clinical reasoning. Team-based learning (TBL) was proposed to improve the students’ ability in clinical reasoning as it is applying a course concept of real complex scenarios. In this study, we aimed to assess and compare the effects of TBL and LBL of postpartum hemorrhage topics on the clinical reasoning and classroom engagement of midwifery students in Indonesia. Methods We conducted a cluster randomized controlled trial to compare the effects of TBL and LBL. The unit was schools and random allocation was conducted using a simple random sampling method (i.e., coin flipping). There was 1 cluster in the intervention group (n = 62 students) and 1 cluster in the control group ( n = 53 students). The students in the intervention group participated in a TBL class (90 min) three times, whereas the students in the control group attended an LBL class on postpartum hemorrhage topics. The primary outcome was the clinical reasoning on postpartum hemorrhage score measured at pre-test, post-test, and 2 weeks post-test. The secondary outcome was Classroom Engagement Survey (CES) score measured after each class finished. We used an unpaired t-test to evaluate the differences between the two groups. The baseline characteristics of the participants were compared using standardized difference. Results We evaluated a total of 115 participants. Regarding the baseline characteristics, there was a small difference in the age, Grade Point Average and knowledge at pre-test between the intervention and control groups. The mean clinical reasoning on postpartum hemorrhage scores were significantly higher in the TBL students than in the LBL students at post-test ( p < .001; Cohen’s d = 1.41) and 2 weeks post-test ( p < .001; Cohen’s d = 1.50). The CES showed a significantly higher in the intervention group than in the control group. Conclusions TBL is an effective learning method for enhancing the clinical reasoning ability of students. This learning method allows for more independent and active learning. Having a strong background knowledge, and discussing cases comprehensively with peers can sharpen the clinical reasoning ability of students.